Mechanical cue‐induced YAP instructs Skp2‐dependent cell cycle exit and oncogenic signaling. (3rd July 2017) - Jang, Wonyul; Kim, Tackhoon; Koo, Ja Seung; Kim, Sang‐kyum; Lim, Dae‐Sik
Abstract: Mechanical tensions are usually generated during development at spatially defined regions within tissues. Such physical cues dictate the cellular decisions of proliferation or cell cycle arrest. Yet, the mechanisms by which mechanical stress controls the cell cycle are not yet fully understood. Here, we report that mechanical cues function upstream of Skp2 transcription in human breast cancer cells. We found that YAP, the mechano‐responsive oncogenic Hippo signaling effector, directly promotes Skp2 transcription. YAP inactivation induces cell cycle exit (G0) by down‐regulating Skp2, causing p21/p27 to accumulate. Both Skp2 reconstitution and p21/p27 depletion can rescue the observed defect in cell cycle progression. In the context of a tissue‐mimicking 3D culture system, Skp2 inactivation effectively suppresses YAP‐driven oncogenesis and aberrant stiff 3D matrix‐evoked epithelial tissue behaviors. Finally, we also found that the expression of Skp2 and YAP is positively correlated in breast cancer patients. Our results not only reveal the molecular mechanism by which mechanical cues induce Skp2 transcription, but also uncover a role for YAP‐Skp2 oncogenic signaling in the relationship between tissue rigidity and cancer progression. Synopsis: The cell cycle regulator and F‐box protein Skp2 is a direct target of the Hippo pathway effector YAP, and required for YAP's oncogenic activity upon mechanoregulation. Mechanical cues function upstream of Skp2 transcription. YAP and TEAD directly promote Skp2 transcription in response to mechanical cues. YAP inactivation induces cell cycle exit (G0) by down‐regulating Skp2, causing accumulation of p21/p27. Both Skp2 reconstitution and p21/p27 depletion rescue the defective cell cycle progression. Skp2 inactivation suppresses YAP‐driven tumor‐spheroid‐like acini and aberrant tissue behaviors in a 3D stiff matrix. YAP and Skp2 expression positively correlate in breast cancer patients. Abstract : YAP links mechanical stress and Skp2 transcription to instruct cell cycle progression and oncogenic functions in breast cancer growth.